The Importance Of Early Child Drug Education; Indonesian Regulatory Perspective - Widjaja, Gunawan (Advances in Social Sciences Research Journal, 2020)
Drug abuse can be happened to anybody. Drug abuse can cause systematic destruction to the sustainability of a state. It is especially important that children and teenager should be avoided from using drugs. There are many kinds of approaches that can be done. One among them was an early education against drug abuse. This research aimed to elaborate the importance of early child drug education and try to provide solutions on how the education must be conducted, based on Indonesian laws and regulations. Data used in this research were of secondary data, which mainly consisted of primary legal sources and secondary legal sources. Data were obtained through literature review using “google” search machine. Data were analysed using deductive “legal reasoning” method, with qualitative approach. Research found that in many jurisdictions, children have been introduced, exposed, and misuse several kinds of drugs. To avoid it, state shall initiate and provide support through education. It may involve formal or informal education institutions. Research also found that early drugs education for children would be good to provide early knowledge to the children so that they can avoid misusing drugs. However, it must be taught by competent person to avoid mis-reception. Indonesia shall has enough sources to implement it. Under current prevailing legislations, Indonesia shall have enough support to start the education. Though Indonesia has sufficient laws and regulations, however Indonesia still needs good system, competent human resources, technologies, facilities, infrastructure, and enough financing to implement the laws and regulations. Inter-departmental cooperation must be set up to support the implementation.